Transforaminal Epidural Injection with Local Anesthesia and Steroid for Single-level Radiculopathy and Pain Score: A Prospective Study in the Tertiary Center of Western Nepal - Shrestha, Sabin; Karki, Prateek; Shrestha, Dinesh Kumar; Yogi, Sushil; Kandel, Sandip (Journal of Nepalgunj Medical College, 2024)
Introduction: Radiculopathy resulting from prolapse of intervertebral disc commonly at L4-L5 and L5-S1, the prominent cause of low back pain affecting daily activities and has a significant socioeconomic burden. Hence, this needs to be addressed with a prominent solution, of which, the transforaminal epidural steroid injection has been one of the promising solutions these days. Aims: To assess the short term and long-term pain relief after transforaminal epidural steroid injection. Methods: 58 patients with radiculopathy at the single level of the lumbar or lumbosacral region were included for transforaminal epidural steroid injection with local anesthesia. Visual analog score, pain score was recorded before, in 15 minutes and four weeks after the steroid injection under C-arm guidance. Statistical analysis was done on the basis of Wilcoxon Signed Ranks Test, Spearman’s correlation test. A p-value < 0.05 was considered to be statistically. Results: The change in Visual Analog Score from the time of presentation in relation to short and long term was significant, viz; VAS0 VAS15m p<0.5 and VAS0/VAS4wks was p<0.5. There was a positive correlation between immediate pain relief and long-term pain reduction however it was not significant (r=0.28, p=0.10) Conclusion: This study suggested the improvement of symptoms with transforaminal epidural steroid injection with local anesthesia and showed a positive correlation between immediate and long-term relief of pain, however it may not be significant.